Performance evaluation of equivalent forwarding sets in software defined networking. (1st March 2020) - Yang, Liang; Ng, Bryan; Seah, Winston K.G.; Singh, Deepak
Abstract: Software-Defined Networking (SDN) allows the forwarding sets to be constructed from forwarding rules which are expressed in the form of a single table or multiple linked tables. To reconcile the forwarding behavior of different flow tables, forwarding sets are converted to canonical form also called as equivalent forwarding set (EFS) . In this paper, two EFS conversion approaches: match-field oriented approach (MFA) and action oriented approach (ACA) are verified through performance evaluation in various functional test scenarios. Using the concept of Boolean reasoning, we prove the correctness of conversion from multiple-flow-table (MFT) to its equivalent MFA and ACA . Similarly, from our experiment on Open vSwitch, the performance evaluation showed that the ACA approach which converts a forwarding set into an action-indexed dictionary performed well with the truth-table based expression. The performance evaluation shows that the MFA approach which converts a forwarding set into a match-field-indexed dictionary is easier to implement in real network devices with smaller storage capacities. Graphical abstract: Image 1 Highlights: Forwarding sets are converted to equivalent forwarding set (EFS). Two EFS approaches are match-field oriented (MFA) and action-oriented (ACA). MFA and ACA are verified through performance evaluation using Boolean Reasoning. The performance evaluation showed the MFA is easier to implement than the ACA.